IDENTIFIKASI BAKAT ATLET FUTSAL MENGGUNAKAN METODEANALYTIC HIERARCHY PROCESS (AHP) - Mohamad Riva Aldoris, - (2024)
ABSTRACT This study aims to identify the talents of futsal athletes using the Analytic Hierarchy Process (AHP) method. The AHP method is used in this study to measure and prioritize important criteria related to the talent of futsal athletes. This study uses mixed-methods research (MMR) which involves quantitative and qualitative methods. The sample in this study amounted to 25 experts in the sport of futsal, including 10 coaches and 15 athletes who have more than 7 years of experience in the field of futsal. Data was obtained through a questionnaire distributed online via google form. The criteria evaluated included anthropometric aspects, biomotor aspects, and somatotype aspects. From the expert assessment in the sport of futsal in this study, it produces the most suitable sub-criteria in conducting talent identification tests. The results of data analysis using AHP get fourteen sub-criteria which have the following percentages: 9.2% VO2Max, 9.2% mesomorph, 9.2% body mass index, 9.2% body weight, 9.1% height, 7.4% ectomorph, 7.1% agility, 6.6% leg muscle strength, 6.5% strength, 6.0% speed, 5.8% leg length, 5.7% flexibility, 4.7% body fat, 4.3% endomorph. Based on the results of data analysis, it can be concluded that there are four most important criteria, namely VO2Max from the biomotor aspect, mesomorph from the somatotype aspect and BMI and body weight from the anthropometric aspect. ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi bakat atlet futsal dengan menggunakan Metode Analytic Hierarchy Process (AHP). Metode AHP digunakan dalam penelitian ini untuk mengukur dan memprioritaskan kriteria-kriteria penting yang berkaitan dengan bakat atlet futsal. Penelitian ini menggunakan mixed-methods research (MMR) yang melibatkan metode kuantitatif dan kualitatif. Sampel dalam penelitian ini berjumlah 25 orang ahli dalam cabang olahraga futsal, diantaranya 10 orang pelatih dan 15 orang atlet yang memiliki pengalaman lebih dari 7 tahun di bidang cabang olahraga futsal. Data diperoleh melalui kuisioner yang disebarkan secara online melalui google form. Kriteria yang dievaluasi termasuk aspek antropometrik, aspek biomotor, dan aspek somatotype.Dari penilaian ahli dalam cabang olahraga futsal pada penelitian ini menghasilkan sub-kriteria yang paling sesuai dalam melakukan tes identifikasi bakat. Hasil analisis data menggunakan AHP mendapatkan empat belas sub-kriteria yang memiliki presentase sebagai berikut: 9.2% VO2Max, 9.2% mesomorph, 9.2% index massa tubuh, 9.2% berat badan, 9.1% tinggi badan, 7.4% ectomorph, 7.1% kelincahan, 6.6% kekuatan otot kaki, 6.5% kekuatan, 6.0% kecepatan, 5.8% panjang kaki, 5.7% kelentukan, 4.7% body fat, 4.3% endomorph. Berdasarkan hasil analisis data dapat disimpulkan bahwa terdapat empat kriteria terpenting yaitu VO2Max dari aspek biomotor, mesomorph dari aspek somatotype dan IMT serta berat badan dari aspek antropometri.